Governance through ?public utilities' models: a regional social interaction approach - Immacolata Caruso; Tiziana Vitolo (European Regional Science Association (ERSA), 2003)
Based on neo-regionalist literature, this paper put on the foreground the importance of public utilities in the “governance” processes. New economic and cultural trends need the abandon of a hierarchical model of government in favour of the governance model, based on organizational structures of partnership and/or of open market. A first step in governance process is the decentralization, or “decentralizing governance”, that is to restructure and to reorganize local authority with the creation of a system of co-responsibility among institutions at the central, regional and local levels according to the principle of “subsidiarity”, and public, private or civil stakeholders. A typical public domain service, the public utilities management, become a crucial issue in order to identity and measure “governance” quality in different local contexts. The paper compares three different typologies in the public utilities market and their effects on the “governance” process. A first typology is based on tenders enhancing the concurrence among local and foreign actors for gaining the assets of the local services; a second one is based on the “project financing strategy”, involving a cooperation mechanism between public and private sector: this model is diffused all over the world; a third one is focused on the sharing of the whole local services branch among a number of contractors, each one assuring the best of efficiency in its field. Finally, the paper aims identifying “actors” and “items” of the governance model involved in public utilities management and giving also indications and suggestions for the implementation of local strategies and policies in order to enhance cooperative connections among suppliers, subcontractors and customers.
Keywords: 330